The prevalence of uterine fibroids in Sverdlovsk region: A retrospective study - Olga Y. Sevostyanova; Tatiana V. Chumarnaya; Natal'ia E. Sevostyanova; Sergei R. Belomestnov; Tat'iana A. Oboskalova; Olga D. Striganova (IP Berlin A.V., 2024)
Aim. To analyze the dynamics of the incidence and prevalence of uterine fibroids (UF) in the population of women in the Sverdlovsk region (SR) and the municipality of Yekaterinburg. Materials and methods. A study was conducted on the incidence and prevalence of UF in rural and urban women aged 18 years and over in 2016-2022. The data from Table No. 3000 of the Federal Statistical Observation Form No. 12 "Information on the number of diseases registered in patients living in the service area of a medical organization" were analyzed. When calculating the indicators, the average annual number of women aged 18 years and over in 2016-2022 was used, the values were expressed in 0/0000. Results. It was found that the incidence of UF in SR was 149.11 0/0000, in the city - 130.89 0/0000 in 2016. There was an increase in the incidence of UF in the SR and the city by 1.93 and 1.96 times in 2019, respectively, compared with 2016 (p0.001). The average growth rate (AGR) of incidence in the SR and the city was 24.6 and 25.2% respectively, and had a pronounced growth dynamics in 2016-2019. The prevalence of UF in SR was 735.8 0/0000, in the city - 650.74 0/0000 in 2016. Subsequently, the dynamics of the increase in prevalence, similar to the incidence, was observed. The prevalence rate in the region was 15.5%, in the city - 11.6% in 2016-2019. There was a decrease in the incidence of UF in SR (p=0.014) and the city (p0.001) in 2020-2022. The AFR had a negative value: -3.4 and -7.9%. The prevalence of UF corresponded to a moderate trend, taking into account the positive values of AFR: 1.3% in SR and 2.3% in the city. Conclusion. The prevalence of UF in SR and the city of Yekaterinburg in the pre-pandemic period (2017-2019) was characterized by a marked increase compared to the initial 2016 year. During the pandemic, there was a slight dynamics in the city and stagnation of the indicator in the SR due to a pronounced decrease in incidence.